Leadership styles and organizational commitment with mediation of organizational citizenship behavior among Bahraini managers - Zainuddin, Mohamed Abdulaziz; Asaari, Muhammad Hasmi Abu Hassan (Center for Promoting Ideas (CPI), 2020)
This study explores the role of organizational citizenship behavioras a mediating variable to the relationship between leadership styles and organizational commitment among Bahraini managers. Organizational citizenship behaviorwas in debate regards it is positive and negative consequences through the literature, most ofthe studies support the conclusion of organizational commitment that leads to organizational citizenship behavior, other studies support the opposite. However, the mediating relationship of organizational citizenship behaviorsbetween leadership styles and organizational commitment is not developed by previous studies.Therefore, the use of the mediating variable gives more insight into the relationship between the dependent and independent variables and contributes to the clarity of conclusions. This study found thatleadership presentsa positive significant relationship with organizational commitment and organizational citizenshipbehavior, and organizational citizenship behavior positively and significantly affects organizationalcommitment and partially mediates the relationship between the two variables